2021
DOI: 10.1101/2021.11.01.21265592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome Wide Association Metanalysis Of Skull Bone Mineral Density Identifies Loci Relevant For Osteoporosis And Craniosynostosis

Abstract: Skull bone mineral density (SK-BMD) provides a suitable trait for the discovery of genes important to bone biology in general, and particularly for identifying components unique to intramembranous ossification, which cannot be captured at other skeletal sites. We assessed genetic determinants of SK-BMD in 43,800 individuals, identifying 59 genome-wide significant loci (4 novel), explaining 12.5% of its variance. Pathway and enrichment analyses of the association signals resulted in clustering within gene-sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Still, the function for many of these genes is unknown, especially whether it is relevant to bone homeostasis. Very recently, Medina-Gomez et al performed the largest skull-BMD-GWAS meta-analysis involving 43,800 individuals, identifying 59 loci, from which four loci were novel [ 7 ]. Using functional studies in zebrafish, the authors demonstrated that skull-BMD GWAS has great potential to help uncover genes important in developmental craniofacial conditions, such as craniosynostosis [ 7 ].…”
Section: Large Gwas and Wgs Have Identified Multiple Loci Associated ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Still, the function for many of these genes is unknown, especially whether it is relevant to bone homeostasis. Very recently, Medina-Gomez et al performed the largest skull-BMD-GWAS meta-analysis involving 43,800 individuals, identifying 59 loci, from which four loci were novel [ 7 ]. Using functional studies in zebrafish, the authors demonstrated that skull-BMD GWAS has great potential to help uncover genes important in developmental craniofacial conditions, such as craniosynostosis [ 7 ].…”
Section: Large Gwas and Wgs Have Identified Multiple Loci Associated ...mentioning
confidence: 99%
“…Very recently, Medina-Gomez et al performed the largest skull-BMD-GWAS meta-analysis involving 43,800 individuals, identifying 59 loci, from which four loci were novel [ 7 ]. Using functional studies in zebrafish, the authors demonstrated that skull-BMD GWAS has great potential to help uncover genes important in developmental craniofacial conditions, such as craniosynostosis [ 7 ]. Remarkably, this work showed that the majority of genes involved in skull homeostasis and intramembranous ossification also play a role in the maintenance of the remaining skeleton and are equally important to understanding the biology of osteoporosis.…”
Section: Large Gwas and Wgs Have Identified Multiple Loci Associated ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, ZIC1 had been related to craniofacial developmental defects [ 3 ]. Its function was further assessed in a large-scale GWAS meta-analysis focusing specifically on BMD variation in the skull, finding 4 novel loci among 59 with genome-wide significance, including ZIC1 [ 4 ]. The gene was further screened in zebrafish crispants that displayed low skull BMD and abnormal suture patterning [ 4 ].…”
Section: Introductionmentioning
confidence: 99%